Tradition of Haul and The Formation Of Social Solidarity and Religiosity in The Community : (Case Study: Haul Remembrance Of Mbah Idris in Karangmalang Village) - Ahmad Nurul Huda; Muhammad Ichrom; Fathan Ghifari Saifuddin (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research examines the Haul tradition as a means of forming social solidarity and religiosity in the community in Karangmalang Wetan Village. The Haul tradition, which is celebrated every year in memory of Mbah Idris, involves the active participation of the local community and produces various interesting social phenomena. This research uses a qualitative approach to describe in depth how this tradition strengthens social relations and increases religious awareness and faith. The research results show that the Haul tradition not only functions as a religious ritual, but also as a tool for spiritual introspection, respect for meritorious figures, and the creation of inner peace and tranquility for society. Social solidarity in this tradition is seen through community mutual cooperation in event preparation and voluntary participation without coercion. Overall, the Haul tradition in Karangmalang Wetan plays an important role in maintaining religiosity and social harmony in the community.